Defect‐Enriched Nitrogen Doped–Graphene Quantum Dots Engineered NiCo2S4 Nanoarray as High‐Efficiency Bifunctional Catalyst for Flexible Zn‐Air Battery. Issue 44 (12th September 2019) - Liu, Wenwen; Ren, Bohua; Zhang, Wenyao; Zhang, Maiwen; Li, Gaoran; Xiao, Meiling; Zhu, Jianbing; Yu, Aiping; Ricardez‐Sandoval, Luis; Chen, Zhongwei
Abstract: Flexible Zn‐air batteries have recently emerged as one of the key energy storage systems of wearable/portable electronic devices, drawing enormous attention due to the high theoretical energy density, flat working voltage, low cost, and excellent safety. However, the majority of the previously reported flexible Zn‐air batteries encounter problems such as sluggish oxygen reaction kinetics, inferior long‐term durability, and poor flexibility induced by the rigid nature of the air cathode, all of which severely hinder their practical applications. Herein, a defect‐enriched nitrogen doped–graphene quantum dots (N‐GQDs) engineered 3D NiCo2 S4 nanoarray is developed by a facile chemical sulfuration and subsequent electrophoretic deposition process. The as‐fabricated N‐GQDs/NiCo2 S4 nanoarray grown on carbon cloth as a flexible air cathode exhibits superior electrocatalytic activities toward both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), outstanding cycle stability (200 h at 20 mA cm −2 ), and excellent mechanical flexibility (without observable decay under various bending angles). These impressive enhancements in electrocatalytic performance are mainly attributed to bifunctional active sites within the N‐GQDs/NiCo2 S4 catalyst and synergistic coupling effects between N‐GQDs and NiCo2 S4 . Density functional theory analysis further reveals that stronger OOH* dissociation adsorption at the interface between N‐GQDs and NiCo2 S4 lowers the overpotential of both ORR and OER. Abstract : A highly efficient and flexible bifunctional air cathode is successfully constructed by defect‐enriched nitrogen doped–graphene quantum dots engineered 3D NiCo2 S4 nanoarray, which exhibits excellent electrochemical activity and long‐term durability. Importantly, the obtained rechargeable and flexible Zn‐air battery shows high power density, outstanding cycle stability, and excellent mechanical flexibility, making it a promising candidate for powering portable/wearable devices.